The Moon, Sun and Jupiter coordinates and distances variation through 100 years - Almohammadi , Abdulrahman H.S.; Qahtan , Atared Y. (Iraqi Journal of Science, 2021)
In this research calculate the ecliptic and equatorial coordinates for the Moon , Sun and Jupiter through 100 years and calculate the distances between the Moon and the Earth , the Sun and the Earth , Jupiter and the Sun, Jupiter and the Earth . From Calculation and discussion the changes in the equatorial coordinate were: Δ , Δ δJ = (22.73+21.93, 23.28+22.99) , and the maximum values and minimum values for the Moon were: Rm(min) = 0.00239,0.00240 and Rm(max) = 0.0027,0.00272 , and Jupiter RJ(min) = 4.99077,4.99966 and RJ(min) = 5.44469,5.45057 , and the periods change preface to calculate the conjunction of the Moon and Jupiter.